Answer:
6(3) - 4 + (3)^2
Explanation:
We will do this on two steps:
1- get g(x)-f(x)
2- substitute with x = 3
Step 1:
f(x) = 4-x^2
g(x) 6x
g(x) - f(x) = 6x - (4 - x^2)
= 6x - 4 + x^2
Step 2:
Substitute with x = 3 as follows:
g(x) - f(x) at x = 3 is:
6(3) - 4 + (3)^2
Hope this helps :)
Just subtract 622 feet from 486 feet to get the change in elevation. The result will be negative because your friend's house is at a lower elevation than yours.
Now find the mean change in elevation per mile by dividing (486 ft - 622 ft) by 4 miles:
-136 ft
----------- = -34 ft/mile
4 mi
Answer:
9.77 metros
Step-by-step explanation:
Ay que usar sine, mira el problema en la photo
Answer:
96 gallons
Step-by-step explanation:
32 divided by 4 = 8 gallons per load
8 x 12 = 96